Are there institutional differences in the earnings of Australian higher education graduates? - Koshy, Paul; Seymour, Richard; Dockery, Alfred Michael (The Economic Society of Australia, 2016)
This paper examines the effect of university quality, as proxied by institutional groupings, on the earnings outcomes of Australian university qualified persons. It uses data from the Household, Income and Labour Dynamics in Australia (HILDA) survey to examine the impact of a variety of factors on earnings, including: institution grouping, gender, age, field of study and industry of employment. The paper reports strong evidence for large and significant field of study and industry effects on the earnings of university graduates. There is no significant evidence for the existence of an institutional effect in Australia, save for a minor effect in relation to regional universities. However, splitting the sample along gender lines reveals some evidence for negative earnings premiums for females in universities outside the Group of Eight and Australian Technology Network, with no such observed effects among males. Overall, the findings indicate a relatively muted earnings effect across Australian university groupings.